SINTESIS 1-(3,4-METILENDIOKSIFENIL)-2-PROPANOL VIA REAKSI OKSIMERKURASI-DEMERKURASI - Gugule, Sanusi (Jurnal Entropi, 2007)
A study has been carried out to synthesis of 1-(3,4-methylenediooxy-phenil)-2-propanol from safrole (isolated from oil of lawang). The synthesize was done using react the oxymercurationdemercuration by means of mercury of acetate and sodium of boron hydride, while identifying conducted with the liquid gas chromatography and spectrometer. The experimental result show that the percentage yield of 1-(3,4-methylenediooxyphenil)-2-propanol was 77,78%.